Late Presentation of Pulmonary Artery-Left Atrial Appendage Fistula Formation After Left Atrial Appendage Device Closure - Miller, Wayne H. (JACC Case Rep, 2020)
Atrial fibrillation is the most common arrhythmia in clinical practice with indication for anticoagulation in those patients whose annual risk for thromboembolism is >2%. Left atrial appendage closure is growing as an alternative to anticoagulation. We present a case of pulmonary artery-left atrial appendage fistula seen after left atrial appendage closure. (Level of Difficulty: Intermediate.)